Analisis Kekuatan Two Blades Propeller APC 9×6 Berbahan Resin Tan dengan Metode 3D Printing Streolithography - Muhammad Farhan; Bhima Shakti Arrafat; Lilies Esthi Riyanti (Langit Biru: Jurnal Ilmiah Aviasi, 2022)
This study aims to analyze the strength of the propeller on an unmanned aerial vehicle (UAV) using additive manufacturing method with Stereolithography (SLA). In this study, testing was conducted by examining the tensile and bending strength of the propeller using a Universal Testing Machine. The results showed that the structural strength of the propeller made of Tan resin applied to the propeller with a 100% infill percentage configuration was better than other 50% infill percentage configurations. The highest tensile strength result was obtained with 100% infill at a value of 133.8 MPa, while the highest bending strength result was also obtained with 100% infill at a value of 2.76 MPa. This research provides an important contribution to the development of additive manufacturing technology in the manufacturing industry, particularly in the production of propellers for UAVs with optimal strength.